Changes in pediatric obesity rates before and during the COVID pandemic in a Federally Qualified Health Center - Madeline T. Moriarty; William R. Law; Jeremy Nadolski; Lester Hockenberry (Preventive Medicine Reports)
Objectives: The changes with pediatric obesity rates during the COVID pandemic with patients from Federally Qualified Health Center (FQHC) clinics are underrepresented in the literature. FQHC patients are often subject to many adverse social determinants of health (SDOH). We sought to characterize changes in obesity rates and weight categories amongst children at a FQHC, comparing a COVID pandemic cohort to a pre-pandemic cohort. Methods: FQHC retrospective clinic data were analyzed for two separate cohorts of children aged 4 to 5 years: Pre-pandemic (2016–2019) and Pandemic (2019–2022). BMI values, BMI percentiles, and obesity rates were compared. Changes between weight categories for individual children were compared. Study participant SDOH related data was obtained from the electronic records, including individual zip codes. Aggregate study entry obesity rates for both cohorts were significantly greater than the national obesity rate. Results: During each cohort's three-year period, BMI values increased significantly. There was no significant difference between the cohorts in these changes. Analysis of individual children's changes in weight categories revealed that significantly more children in the pandemic cohort demonstrated shifts between obese and other weight categories compared to the pre-pandemic cohort during comparable 3-year study periods. Conclusions: This study is one of the first to investigate the details related to the changes with weight categories with a FQHC pandemic cohort. We suggest that these patterns warrant further study into the complex interactions of health inequities that are related to race and social determinants of health, aggravated by public health crises such as the COVID pandemic.